Anos 60, anos 90 : a crítica cinematográfica brasileira "pós-retomada" e a tradição moderna - Nogueira, Cyntia Araújo (2007)
An analysis of the dialogue established by an influential stream of the Brazilian film criticism from the 90s with the modern critical tradition founded in the Cinema Novo period of the 60s. The aim of this work is to investigate the permanency of analytical and ideological parameters that respond to a different political, economic, social and cultural contexts, contesting its consequences for the discourses constructed about the production of the past decade and the beginning of this century